Épocas de semeadura, genótipos e programas de controle químico no manejo integrado da brusone na cultura do arroz irrigado - Pinto, Felipe Frigo (2015)
The blast is the main disease of flooded rice. The integrated management of this disease is based on the adoption of cultural, genetic and chemical strategies of control. The objective of this work was to evaluate the effect of eight chemical control programs of Pyricularia oryzae applied on IRGA 424, IRGA 428, GURI INTA CL, PUITA INTA CL, QM 10 10 CL and INOV CL rice varieties, and 10/30/2013 and 11/26/2013 sowing times. This work was conducted in the 2013/2014-crop season, under field conditions, in lowland area in Sao Sepé, RS, Brazil. The treatments were arranged in a randomized experimental blocks design, in a split plot and five replications. The variables analyzed were AUCPD on the flag leaf and entire plant, panicle blast, yield and the whole grains percentage. The delay in sowing date increased significantly the incidence and severity of the blast in flooded rice. IRGA 424, IRGA 428 and QM 10 10 CL showed resistance to Pyricularia oryzae, while the GURI INTA CL, PUITA INTA CL and INOV CL were susceptible. The addition of Tricyclazole fungicide to Kresoxim-methyl + Epoxiconazole fungicides is critical to the efficient control of Pyricularia oryzae. The applications of fungicides in the R1 + R2 + R4 and R2 + R4 stages are the most effective in the chemical control of rice blast. The integration among cultural, genetic and chemical methods is critical to the efficient management of blast in flooded rice.